1977
DOI: 10.1017/s0001566000009685
|View full text |Cite
|
Sign up to set email alerts
|

Genetic and Extragenetic Variance In Motor Performance

Abstract: A simple additive model of genes plus environment, based on intrapair similarities observed in 35 MZ and 35 like-sexed DZ twin pairs, was used to estimate the relative contribution of genetically controlled phenotypic variance in psychomotor individuality. Subjects practiced 50 trials on a pursuit rotor apparatus under a 20-sec/20-sec, work-rest schedule with a 30 min rest pause allowed between trials 30 and 31. Analyses of the data disclosed that a greater proportion of genetic factors, as opposed to nongenet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
4
1

Year Published

1980
1980
2003
2003

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 14 publications
(16 reference statements)
2
4
1
Order By: Relevance
“…Marisi [16], also showed decreases in heritability with practice on the pursuit rotor and, in addition, he found that the contribution of systematic environmental effects (E 2 ) increased as practice progressed, whereas error variance (e 2 ) remained relatively stable. Although these findings are in general accordance with McNemar [17], it should be noted that interpolation of the 30 min rest could have introduced confounding effects of reminiscence and warm-up decrement in the postrest results [1].…”
Section: Review Of Motor Skill Studiessupporting
confidence: 86%
See 1 more Smart Citation
“…Marisi [16], also showed decreases in heritability with practice on the pursuit rotor and, in addition, he found that the contribution of systematic environmental effects (E 2 ) increased as practice progressed, whereas error variance (e 2 ) remained relatively stable. Although these findings are in general accordance with McNemar [17], it should be noted that interpolation of the 30 min rest could have introduced confounding effects of reminiscence and warm-up decrement in the postrest results [1].…”
Section: Review Of Motor Skill Studiessupporting
confidence: 86%
“…An important study of the heritability of fine motor skill was that conducted by McNemar [17] who tested 47 MZ and 46 DZ pairs on five different tasks (pursuit rotor, arm steadiness, speed drill, spool packing, card sorting). He found consistently higher intrapair correlations for MZ than for DZ twins (0.71 to 0.95 vs 0.39 to 0.56).…”
Section: Review Of Motor Skill Studiesmentioning
confidence: 99%
“…Marisi (20) found that the heritability for performance on a pursuit-rotor task decreased over 30 practice trials (from an initial 0.79 down to 0.35), in agreement with McNemar's early findings, back in 1933 (21), that exercise did not modify the degree of similarity of MZ co-twins but increased that of DZ co-twins, thus decreasing heritability estimates. On the other hand, Williams and Gross (34) showed that the heritability for a stabilometer task increased after a two-day practice (from 0.27 to 0.69), and remained close to this final level for the next four days.…”
Section: Introductionsupporting
confidence: 83%
“…A number of twin studies were conducted in the past on such aspects as sport participation, motor skills, and learning (Gedda, 1955(Gedda, , 1960Grebe, 1955;Kovar, 1975Kovar, , 1981Marisi, 1977;Sklad, 1972Sklad, , 1975Weiss, 1979), motor performance (Bouchard et al, 1986;Fagard et al, 1991;Klissouras, 1971), and response to training (Hamel et al, 1986;Proud'Homme et al, 1984;Saltin, 1969), but the determinants of motor performance are still far from clarified. In this context, the collection of a large representative series of twins who are also athletes with years of training, and the identification of top-level twin athletes to be studied directly in detail, can provide a unique resource for further research on such issues as heritability versus training in top-level performance, response to training programs, ages that can best be trained, functional adaptation, and so forth.…”
Section: Research Applicationsmentioning
confidence: 99%